Program Makan Bergizi Gratis dalam Perspektif Politik Legislasi: Analisis Risiko Hukum dan Beban Fiskal Negara - Ade Saputra Dinata; Meydilah Ayunafisah; Vera Ayu Lestari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The government policy known as the Free Nutritional Meal Program (MBG) aims to improve public nutrition and reduce stunting rates in Indonesia. The purpose of this study is to examine the MBG Program from a political perspective, particularly considering political dynamics, legal risks, and fiscal issues. This research was conducted through literature review, reviewing various journals and academic sources. The results indicate that the MBG not only has social impacts but also influences political interests, poses risks to legal enforcement, and disrupts the sustainability of the state budget. Therefore, for the program to be successful and sustainable, strong regulations and oversight are required. Furthermore, this populist program is often utilized as an instrument for power legitimacy, demanding compromises between the executive and legislative branches during its budget approval process. Without a detailed legal framework, the policy's implementation is highly vulnerable to overlapping institutional authority and potential misappropriation of funds. Ultimately, technology-based monitoring strategies and accountable governance are the main keys to maintaining the stability of the State Budget (APBN).